PENEGAKAN HUKUM PEMERINTAHAN TERHADAP IZIN PEMERINTAHAN GELANGGANG PERMAINAN DI KOTA PEKANBARU - Ferri Malsa; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
To enforce the Government Law against the game arena government permit in Pekanbaru City, the Civil Service Police Unit plays its role as an enforcer of regional regulations. Government law enforcement is also expected to have an orderly, safe and peaceful and harmonious atmosphere within the framework of community, nation and state life. The formulation of the problem taken is how to enforce government law on game arena permits in Pekanbaru City in 2018 - 2019 and what are the inhibiting factors on the enforcement of Government Law on game arena government permits in Pekanbaru City in 2018 - 2019.               The purpose of this study is to first find out how the Pekanbaru City government law enforcement against the abuse of the authority of Game Customers. To find out what are the obstacles that occur against the enforcement of government law against the permission of the government playing games in the city of Pekanbaru. The research method used is qualitative research. This type of research is descriptive qualitative. The location of this research is Pekanbaru City Civil Service Police Unit and DPMPTSP Pekanbaru City. Data collection techniques by observation, interview and study documentation. Data analysis techniques by data reduction, data presentation and data verification.               The results of the study show that for the enforcement of government law against the permits of the Games Arena in Pekanbaru, the city uses several types of sanctions that are used: Governmental Coercion (Bestuuesdwang), Withdrawal of Decision (Stipulation), Imposing Forced Money (Dwangsom) and Imposing Administrative Fines. Barriers that occur against law enforcement Misuse of licensing game interference in the city of Pekanbaru is a regulation that has been used for too long. Deceiving law enforcement officers with the Rink Arena children's games to test dexterity. The existence of law enforcers involved as guards in the Games which indicated gambling. Lack of Legal Awareness for Game Arena and Community Business owners. Factors for some people who still consider gambling to be a normal thing.